O10.4. THE ROLE OF CONTEXTUAL FACTORS AND ASSESSMENT STRATEGIES IN THE ACCURATE SCREENING OF PSYCHOSIS-RISK SYMPTOMS. (18th May 2020) - Schiffman, Jason; Rakhshan Rouhakhtar, Pamela; Millman, Zachary; Thompson, Elizabeth; Phalen, Peter
Abstract: Background: Falsely observing symptoms of psychosis risk in youth is a critical limitation to pluripotent prevention efforts. Factors including race, age, and measurement construction may affect the validity of semi-structured interviews and self-report screening tools designed to identify symptoms. Consideration of different constructs measured within a single screening tool, what a screening tool can offer beyond prediction of psychosis-like symptoms, and how to maximize efficiency may all influence the ability to effectively identify people who would benefit from services. Methods: Help-seeking adolescents (N=134) ages 12–25 completed various screening tools for psychosis risk, and the Structured Interview for Psychosis-risk Syndromes (SIPS). The influence of race and age on screen scores and SIPS (CHR) symptoms were examined. We also evaluated alternatives to CHR symptom screening beyond conventional CHR screening tools. Results: Higher Prime Screen scores increased the probability of clinician assessed symptoms among White participants, but not Black participants (interaction: b = -0.50 Wald χ2[1] = 4.63, p = .03, Exp[B] = 0.60), and younger participants were more likely to use the Prime Screen as a dichotomous (yes/no) screener relative to older participants, reducing screener efficacy (b = -0.04, Wald χ2[1] = 3.75, p = .05, Exp[B] = 0.96). Given discrepancies across groups, we attempted to expand screening strategies. First, to better understand the Prime Screen, factor analysis suggested two distinct factors that appear to measure different constructs. Additionally, an IRT model of several CHR screening tools suggested the value of an ultra-brief two-item measure. Finally, analyses of the BASC-2, a more comprehensive measure of behavior that includes, but is not limited to, psychosis risk items, also demonstrated accurate prediction of psychosis symptoms, as well as more pluripotent conceptualizations of symptoms. Discussion: Results suggest that contextual or individual factors influence the accurate identification of individuals exhibiting psychosis-risk symptoms. Tailored approaches to screening based on an awareness of context, identity, setting, and preferences of clients are possible, and customizing assessment efforts accordingly may be useful for the accurate identification of a variety of people who might benefit from services.